2020
DOI: 10.3390/ijms21175944
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis and Biologic Significance of the β-Dystroglycan-Emerin Interaction

Abstract: β-dystroglycan (β-DG) assembles with lamins A/C and B1 and emerin at the nuclear envelope (NE) to maintain proper nuclear architecture and function. To provide insight into the nuclear function of β-DG, we characterized the interaction between β-DG and emerin at the molecular level. Emerin is a major NE protein that regulates multiple nuclear processes and whose deficiency results in Emery–Dreifuss muscular dystrophy (EDMD). Using truncated variants of β-DG and emerin, via a series of in vitro and in vivo bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…However, the function and consequences of this nuclear translocation are not yet known. It has been demonstrated that β-DG contributes to the stability of the nuclear membrane in murine myoblasts ( Gómez-Monsivais et al, 2020 ), but it has also been highlighted that the translocation of β-DG fragments into the nucleus is associated with alterations in the expression levels of some genes in prostate cancer cells ( Mathew et al, 2013 ). It remains to be clarified if and how nuclear β-DG exerts control over gene expression and whether this is the consequence of an activation of a regulated cascade of signals leading from the external stimuli to the cell response.…”
Section: Dg and Signal Transductionmentioning
confidence: 99%
“…However, the function and consequences of this nuclear translocation are not yet known. It has been demonstrated that β-DG contributes to the stability of the nuclear membrane in murine myoblasts ( Gómez-Monsivais et al, 2020 ), but it has also been highlighted that the translocation of β-DG fragments into the nucleus is associated with alterations in the expression levels of some genes in prostate cancer cells ( Mathew et al, 2013 ). It remains to be clarified if and how nuclear β-DG exerts control over gene expression and whether this is the consequence of an activation of a regulated cascade of signals leading from the external stimuli to the cell response.…”
Section: Dg and Signal Transductionmentioning
confidence: 99%
“…Interestingly, however, the determined localisation of the truncated βDG constructs in this study was not unprecedented. The expression of full-length βDG has been used extensively to study nuclear functions and is routinely observed in an ER-like distribution [ 4 , 11 , 26 , 42 , 43 ]. Confocal analysis of C2C12 myoblasts expressing full-length βDG also indicates its presence throughout the nucleus, though how it escapes the membranous environment is unclear [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMD binds to β-catenin, forming a protein complex which in the presence of EMD loss or malfunction may alter the β-catenin cycle and thus activate the transcription of genes implicated in cell hypertrophy and probably signaling pathways involved in overlap with DCM. β-Catenin is a component of the intercalated discs of the cardiomyocyte, and its alteration modifies the intercellular junctions; it has been suggested that this may be related to atrioventricular conduction disturbances [25,29]. These findings in mice suggest that therapeutic inhibition of the Wnt/β-catenin complex could afford benefit for patients with EDMD [30].…”
Section: Molecular Hypothesismentioning
confidence: 99%